2016
DOI: 10.1097/gox.0000000000001113
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Clavien–Dindo Classification in Understanding the Limitations and Indications of Larynx-preserving Esophageal Reconstruction

Abstract: Background:The Clavien–Dindo (CD) classification is used to evaluate the severity of surgical complications. However, its usefulness in esophageal reconstruction has not been reported. To address this, this case series study used the CD classification to evaluate the complications after cervical esophageal reconstruction with free jejunum transfer or supercharged pedicled intestinal transfer.Methods:All consecutive patients who underwent esophageal cancer surgery with larynx-preserving free jejunum or pedicled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…11 Similarly, a review and a case–control study showed that compared with primary closure, which associates with fistula formation rates of 20–50%, vascularized tissue transfer reduces fistula formation to 15–20%. 12,13 However, if a fistula does develop and flap surgery is performed again to repair it, the risk of complications increases: these complications include infection, donor-site mobility, and flap necrosis, as well as formation of another fistula or relapse of the original fistula.…”
Section: Discussionmentioning
confidence: 98%
“…11 Similarly, a review and a case–control study showed that compared with primary closure, which associates with fistula formation rates of 20–50%, vascularized tissue transfer reduces fistula formation to 15–20%. 12,13 However, if a fistula does develop and flap surgery is performed again to repair it, the risk of complications increases: these complications include infection, donor-site mobility, and flap necrosis, as well as formation of another fistula or relapse of the original fistula.…”
Section: Discussionmentioning
confidence: 98%
“…Free flap transfer is an important procedure in head and neck reconstruction. Many factors dictate the success of this procedure, including flap selection, vascular anastomosis, the flap-suturing method, various considerations made to ensure tracheal and swallowing functions, and postoperative management 1013 Of these factors, microsurgical vascular anastomosis is particularly crucial. However, it should be emphasized here that successful vascular anastomosis does not mean successful surgery: the surgery is successful only if the flap fully restores the lost functions and roles.…”
Section: Discussionmentioning
confidence: 99%
“…This classification is graded I (deviations from the normal postoperative course that does not require intervention), II (deviations requiring pharmacological interventions), III (deviations requiring surgical or invasive treatment), IV (life-threatening deviations), and V (death). 9 In our study, the CD classification was expressed as CDI or CDII and CDIII or higher. The frequency of CDIII or higher cases whose complication was venous trouble that led to flap congestion and salvage surgery was also recorded.…”
Section: Methodsmentioning
confidence: 97%
“…This association is an important issue with regard to esophageal cancer surgery. Recent studies have reported that the Clavien-Dindo classification provides an effective assessment of complications after esophageal cancer surgery [ 17 ]. Postoperative complications using this classification were found to have an impact on patient OS or RFS in two previous studies [ 7 , 8 ], and our findings support the findings of these studies.…”
Section: Discussionmentioning
confidence: 99%